Income Redistribution Effect of Electricity Price Cross-Subsidies and Improvement of Ladder Electricity Price - Siqiang LIU; Na DING; Yingkai SUN; Ze YE; Yongfei WU; Yali WANG (Zhongguo dianli, 2023)
Whether we can “properly handle the cross-subsidies of electricity price” is becoming the key problem throttling the progress of new round of power market-oriented deepening reform. Based on the big data of electricity consumption of residents in Hebei Province in 2017, the price-gap approach, Dagum Gini coefficient and its dividing standard are applied in this paper to empirically analyze the fairness of cross-subsidies of residential electricity price from the perspective of income redistribution. The results show that grouped by the scale of electricity consumption from low to high, residents benefiting the cross-subsidies of electricity price within the group, exhibit a U-shaped fluctuation trend, i.e., high Gini coefficient values at both ends and low values in the middle part of the curve. Moreover, polarized differences are observed between groups. Particularly with the increasing gap of electricity consumption between these groups, the levels of inequality between groups rise as well, and the corresponding Gini coefficient reaches as high as 0.8971. The empirical study shows that the current step price policy results in extremely unfair redistribution effect of cross-subsidy income due to the coarse-grained settings of step quantity and graded electricity quantity. According to the principle of fairness, the improvement of step quantity and graded electricity division are put forward to make the subsidies more precise.